1998
DOI: 10.1523/jneurosci.18-16-06176.1998
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Olfactory Ensheathing Cells Remyelinate and Enhance Axonal Conduction in the Demyelinated Dorsal Columns of the Rat Spinal Cord

Abstract: Olfactory ensheathing cells (OECs), which have properties of both astrocytes and Schwann cells, can remyelinate axons with a Schwann cell-like pattern of myelin. In this study the pattern and extent of remyelination and the electrophysiological properties of dorsal column axons were characterized after transplantation of OECs into a demyelinated rat spinal cord lesion. Dorsal columns of adult rat spinal cords were demyelinated by x-ray irradiation and focal injections of ethidium bromide. Cell suspensions of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
232
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 316 publications
(243 citation statements)
references
References 26 publications
6
232
1
2
Order By: Relevance
“…These cells are unique in that they continue to arise in the olfactory epithelium from which they can migrate to the olfactory bulb throughout life [232][233][234]. Rodent and human OECs generate Schwann-cell-like myelin and improve conduction properties when transplanted to areas of demyelination in the brain or spinal cord [227,233,[235][236][237][238][239][240]. OECs also have the capacity to promote axonal growth [241] and to secrete neurotrophic molecules [242,243].…”
Section: Olfactory Nerve Ensheathing Cellsmentioning
confidence: 99%
“…These cells are unique in that they continue to arise in the olfactory epithelium from which they can migrate to the olfactory bulb throughout life [232][233][234]. Rodent and human OECs generate Schwann-cell-like myelin and improve conduction properties when transplanted to areas of demyelination in the brain or spinal cord [227,233,[235][236][237][238][239][240]. OECs also have the capacity to promote axonal growth [241] and to secrete neurotrophic molecules [242,243].…”
Section: Olfactory Nerve Ensheathing Cellsmentioning
confidence: 99%
“…Following a second centrifugation (2,000 rpm, 15 min), the cells were collected in saline solution. Schwann cells and olfactory ensheathing cells were prepared from adult rats as previously described by Honmou et al (1996) and Imaizumi et al (1998), respectively.…”
Section: Isolation Of Bone Marrow Schwann and Olfactory Ensheathingmentioning
confidence: 99%
“…While the precise mechanism of this functional recovery is not fully understood, several mechanisms have been suggested including remyelination (Devon and Doucette, 1992;Franklin et al, 1996;Imaizumi et al, 1998;Sasaki et al, 2004), long axon tract regeneration (Li et al, 1997;Ramon-Cueto et al, 2000;, axonal sparing (Plant et al, 2002) and plasticity associated with novel polysynaptic pathways (Keyvan-Fouladi et al, 2002;Bareyre et al, 2004). In addition, recruitment of endogenous SCs (Takami et al, 2002;Boyd et al, 2004;Ramer et al, 2004) and remote inhibition of apoptosis of motor cortical neurons (Sasaki et al, 2006a) have been suggested to contribute to improvement in functional outcome in injured spinal cord after OEC transplantation.…”
Section: Introductionmentioning
confidence: 99%